KAJIAN PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA DI PT. SPINDO,Tbk., SURABAYA - Wicaksono, Bintang Cahyoadi (Institut Teknologi Adhi Tama Surabaya, 2024)
Occupational Safety and Health Management System (SMK3) is a labor protection system in preventing and minimizing the risk of material and non-material losses, so that it can support effective and efficient performance improvement. In accordance with PP No. 50 of 2012, one way to prevent work accidents is through the implementation of the Occupational Safety and Health Management System (SMK3). In implementing SMK3, every company is required to carry out five things, namely determining K3 policies, K3 planning, implementing K3 plans, monitoring and evaluating K3 performance, and reviewing and improving SMK3 performance. Research at PT. Spindo, Tbk., is intended to assess the company's readiness to implement SMK3 in the technical aspect according to the standards of Government Regulation 50 of 2012. While the study on the technical aspect was carried out using the SMK3 audit checklist according to the standards of Government Regulation 50 of 2012. The results of the study concluded that in the technical aspect, the company's readiness in implementing SMK3 according to the standards of PP 50 of 2012 achieved a value of 72.8%, or is in the category of good implementation level.